2022
DOI: 10.3390/nano12244387
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic and Electrochemical Performance of CF2-Modified g-C3N4/Graphene Composite Film Deposited by PECVD

Abstract: The physicochemical properties of functional graphene are regulated by compositing with other nano-carbon materials or modifying functional groups on the surface through plasma processes. The functional graphene films with g-C3N4 and F-doped groups were produced by controlling the deposition steps and plasma gases via radio frequency plasma-enhanced chemical vapor deposition (RF-PECVD). The first principles calculation and electrochemistry characteristic of the functional graphene films were performed on Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…2a and b ) lead to the conclusion that both samples are amorphous, albeit the CD1 sample indicated slightly different features, which can be related to the presence of graphene fragments in the particle core. 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a and b ) lead to the conclusion that both samples are amorphous, albeit the CD1 sample indicated slightly different features, which can be related to the presence of graphene fragments in the particle core. 26 …”
Section: Resultsmentioning
confidence: 99%
“…2a and b) lead to the conclusion that both samples are amorphous, albeit the CD1 sample indicated slightly different features, which can be related to the presence of graphene fragments in the particle core. 26 XPS measurements were performed to determine the composition of the samples depending on their synthesis routes. The CD2 XPS survey spectrum features the contribution of only two components, i.e., carbon and oxygen, whereas the CD1 XPS survey spectrum reveals the presence of uorine and nitrogen in addition to carbon and oxygen (Fig.…”
Section: Morphology and Composition Of The Samplesmentioning
confidence: 99%
“…These new peaks were associated with AC-FAS, which further demonstrated that the GP surface has been successfully modified. In addition, the AC-FAS-GP had higher transparency and crumpled morphology, implying that it was a material composed of fewer layers [34]. Its size was relatively large, which signified that it needed further ultrasonic crushing before use.…”
Section: Characterization Of Ac-fas-gpmentioning
confidence: 99%